Antiquity in the Razumovskys’ Art Collection - Naumova, Vera S. (Actual Problems of Theory and History of Art, 2015)
Mid-18th century was characterized by the activity of highly educated commissioners who built their town palaces and country estates in European style, and filled them with paintings, sculptures, and drawings. Count Kirill G. Razumovsky’s (1728–1803) collection was considered to be one of the best in the late 18th century. Paintings with mythological scenes accounted for a considerable part of the art gallery in his palace on the bank of the Moika River in Saint Petersburg. In 1765–1767 Razumovsky travelled around Europe, including Italy, where he had an opportunity to get acquainted with the monuments of ancient Rome and also to replenish his collection. Razumovsky acquired a work from the famous Roman painter Batoni named “Hercules at the crossroads”. Besides, he ordered his portrait where he would be pictured against the background of renowned ancient sculptures “Laocoon with his sons”, “Apollo of the Belvedere”, “Arianne” and “Antinous”. The greater part of the works with mythological scenes were painted by Italian artists — A. Caracci, P. Liberi, P. Pagani, G. Cignaroli, A. Markenzini, etc. Landscapes showing ancient architecture, painted by G. P. Panini, A. Ioli, Ch.-L. Clerisseau, and Allemand, the collector referred to as pieces of great importance. Obviously, Razumovsky’s subsequent commissions must have been influenced by Italian masterpieces — this can be traced in his palaces built after the projects of J.-B. Vallin de la Mothe, G. Quarenghi, Ch. Cameron and other architects of the period.
Keywords: private collecting; art collection; Italian painting; K. G. Razumovsky; collection; art gallery; ancient art; collector